2020
DOI: 10.1017/s1368980020000415
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and food group intakes and skeletal muscle index in the Japanese elderly: a cross-sectional analysis of the NHNS 2017

Abstract: Objective: To examine nutrient and food intakes according to the levels of skeletal muscle mass index (SMI) in the elderly. Design: Cross-sectional study. Setting: Data were derived from the 2017 National Health and Nutrition Survey in Japan. SMI was calculated by dividing appendicular skeletal muscle (or lean) mass (kg) by height squared (m2). We calculated the multivariable-adjusted means of individuals’ dietary intake. Dietary intake of energy, nutrients and food cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…In a 2016 study, it was reported that older, sarcopenic Dutch people have a low intake of vitamin B6 [11]. Similarly, in 2020, older Japanese people with a low skeletal muscle index, which reflects muscle loss, were also found to have a low vitamin B6 intake [9]. It has been hypothesized that the low vitamin B6 intake as well as its low levels in older or sarcopenic people is possibly due to the low intake of proteins, one of the main food sources for vitamin B6, in the elderly [10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a 2016 study, it was reported that older, sarcopenic Dutch people have a low intake of vitamin B6 [11]. Similarly, in 2020, older Japanese people with a low skeletal muscle index, which reflects muscle loss, were also found to have a low vitamin B6 intake [9]. It has been hypothesized that the low vitamin B6 intake as well as its low levels in older or sarcopenic people is possibly due to the low intake of proteins, one of the main food sources for vitamin B6, in the elderly [10].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, among the 13 vitamins for humans, vitamin D is the only one that has been extensively studied at both physiological and cellular levels. However, recent research suggests that other nutrients, such as antioxidants, manganese, vitamin A, vitamin E, and vitamin B6, also play a role in the prevention or improvement of sarcopenia [4,[7][8][9][10][11][12][13]. Recent human studies (2016-2021) in European countries as well as Japan have demonstrated that the low intake and low levels of vitamin B6 coexist with sarcopenia [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations